Kajian Empiris Kepatuhan Wajib Pajak Pengusaha di Kota Banda Aceh - Riza, Akmal (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Empirical studies regarding taxpayer compliance with an obligation and obligation to be carried out for every citizen as fulfillment of citizenship in Indonesia, many business people in Banda Aceh City do not report their tax obligations correctly so that the level of individual taxpayer compliance is low and the tax service office as executor of state duties often conducts socialization so that entrepreneurs have a taxpayer ethic in fulfilling their obligations every year. The aim of the study was to determine the effect of taxpayer ethics on individual taxpayer compliance at KPP Pratama Banda Aceh. The research population is all registered WPOP in the city of Banda Aceh (KPP Pratama) using proportionate strafied random sampling technique on 100 entrepreneurs as respondents. The research findings show that the variable of taxpayer ethics has a positive and significant effect on taxpayer compliance in entrepreneurs in the city of Banda Aceh with the hypothesis that the results of simple regression analysis show that the coefficient value is 0.709 and t-count 9.959> t-table 1.984 and a significant level of p-value 0.000 <0.05.